Circular Polarization Antenna-Filter - S. Bankov; A. Davydov; V. Kalinichev; P. Viugin; A. Kurushin (Advanced Electromagnetics, 2019)
A two-function filtering antenna device in the 1-2 GHz band is investigated. The device radiates or receives electromagnetic waves of circular polarization and simultaneously performs the function of a second-order bandpass filter. The considered design consists of a dual-mode printed antenna-resonator coupled with two non-radiating resonators which are fed by a quadrature balanced power divider. Using the model in the form of an equivalent circuit the main features of the structure synthesis and its tuning are analyzed including potentially achievable characteristics. The results of the numerical simulations using electromagnetic software are presented in comparison with the experimental characteristics for the prototype made of high-permittivity high-quality ceramics. It is found that the proposed design is characterized by an almost two-fold increase of the operating frequency band compared to the resonant antenna itself while maintaining a low level of cross-polarization within the passband. It is also shown that the design has the frequency response of the second-order bandpass filter.